The Impact of Principals' Competence on the Teaching Effectiveness of Primary School Teachers - Hassani, Sanaz Haj; Batmani, Fardin; Hosseinpour, Soheila (International Journal of Psychosocial Rehabilitation, 2020)
The aim of this study was to investigate the effect of principals' competence on teachers' teaching efficacy. The competence of principals was measured in terms of general competence (in terms of ethics and duties) and specific competence (in terms of personality and skills) using descriptive-survey method and the statistical research population included all primary school principals in Semnan province based on the Krejcie and Morgan table (1970). Out of 190 people in Semnan province, 123 people were selected by stratified random sampling method and educational management specialists (professors and doctoral students) and 150 people were selected by simple random sampling method from the whole country. To collect data in this research, a researcher-made competency questionnaire of principals and the questionnaire of teaching effectiveness of teachers by James Jangret et al. (2017) were used. In order to investigate the validity of the questionnaire, the diagnostic methodology of AVE index was used and in order to measure the reliability of the questionnaire, CR combination reliability method with Cronbach's alpha were used. Statistical methods of Spearman correlation coefficient, regression analysis and structural equations were used to analyze the data. The results showed that there was a relationship between the competence of principals and the effectiveness of teacher teaching. In the meantime, the competence of principals and their dimensions were having a positive and significant effect on the effectiveness of primary school teachers' teaching.